EFL STUDENTS’ PERCEPTION ON TOEIC PRACTICE CLASS AT TWELFTH GRADERS SMK KESEHATAN HUSADA PRATAMA - Fauzi, Imam (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
Learning English language is much demanded and crucial for EFL students. Students are supposed to be able to prove their language skills through language proficiency test. TOEIC is one of the language proficiency tests that mostly EFL students especially vocational high school students need to learn and master it. However, the students often encounter some difficulties in conducting the TOEIC test. Improving students’ comprehension about practicing the TOEIC test highly requires a good strategy. TOEIC practice class is considered to be one of appropriate approaches to be applied to encourage the students’ comprehension. The purpose of the research is to investigate comprehensively whether there is any significant improvement of practicing TOEIC strategy on the students’ listening comprehension of the twelfth grade students. This research applied descriptive qualitative approach that engages one group participated by 30 students of twelfth grade of SMK Kesehatan Husada Pratama. It can be seen that there was such significant improvements of practicing TOEIC strategy on the students’ listening comprehension of the twelfth grade at SMK Kesehatan Husada Pratama academic year 2019/2020.